Haemodialysis in 'hepatorenal syndrome': report on two cases. Issue 2 (February 1985) - Keller, F; Wagner, K; Lenz, T; Pommer, W; Hahn, G; Molzahn, M; Krause, P H
Abstract : We report two patients with hepatorenal syndrome who recovered from oliguria and renal failure after temporary treatment with haemodialysis. Hepatorenal syndrome developed under diuretic treatment in both patients. Volume expansion, dopamine, and prostaglandin I2 did not improve renal function. In the one patient with alcoholic cirrhosis, renal biopsy showed only minimal alterations of glomeruli, tubuli, and arterial vessels. In the other case, the deterioration and improvement in renal function parallelled changes in acute alcohol-toxic hepatic function. We conclude that haemodialysis should be considered for treatment of hepatorenal syndrome in selected patients where reversal of liver failure can be expected.